Simulated video-based telehealth training for emergency physicians - Hayden, Emily M.; Nash, Christopher J.; Farrell, Susan E. (Frontiers in Medicine, 2023)
Introduction Little exists in the literature describing video-based telehealth training, especially for practicing Emergency Physicians. Materials and methods This was a retrospective, pre- and post-assessment of physicians’ knowledge and confidence on video-based telehealth after two simulated telehealth encounters. Attending physicians voluntarily participated in Zoom-based trainings and received feedback from the patient actors immediately after each simulation. Post-experience surveys queried participants on the training, aspects of telehealth, and confidence in features of optimal telehealth practice. Results The survey had 100% response rate (13/13 physicians). Participants recommended the simulated training experience, mean of 8.38 (SD 1.89; 0 = Not at all likely, 10 = Extremely likely). Pre- and post-response means increased in two questions: “I can describe at least two ways to improve my video-based clinical care”: delta: 1.54, t(12) = 3.83, p = 0.002, Cohen’s d effect size of 1.06, and “I know when video-based telehealth could be helpful in clinical practice”: delta: 0.99, t(12) = 3.09, p = 0.009, Cohen’s d effect size of 0.86. Conclusion In this pilot, participants viewed telehealth more favorably after the experience and indicated improved confidence in focused telehealth skills. Further study is needed to determine what simulated case content provides the most value for decision-making via telehealth.